Preparing Transitions: The Impact of Vocational Role Models on Occupational Aspirations Within Social Contexts - Eva Böhle; Janina Beckmann; Mona Granato (Social Inclusion)
The formation of occupational aspirations, an important prerequisite of successful school‐to‐work transitions, is embedded in different social contexts, including youths’ families and peers. At the same time, adolescents are guided by various career orientation activities, including vocational role models, that provide them with information on available career options and stimulate career decision‐making. In this study, we combine both strands of research and examine how vocational role model effects unfold in the different social contexts that students are embedded in, potentially enabling or constraining intervention effects. Based on a large‐scale role model intervention study comprising 1,190 students in Germany, we first examine how peer and family contexts are associated with students’ occupational aspirations as key dimensions of social influence. Our results show that both peer and parental social contexts are related to students’ career aspirations, with descriptive peer norms and injunctive peer and parent norms being the most relevant. Second, we show that unique encounters with vocational role models are, on average, related to increased occupational aspirations for the presented occupation, extending previous empirical findings to the VET context. Third, we examine whether and how role modelling interacts with students’ social embeddedness. We do not find statistically significant interactions between the examined social contexts and the role model intervention. Hence, role model effects apply even in contexts that convey strong norms. Nevertheless, we find subtle patterns suggesting that role model effects are more pronounced when peers convey adverse norms and less knowledge regarding an occupation and when peers’ self‐efficacy is high. Theoretical and practical implications are discussed.